Pengaruh Keunggulan Bersaing dan Kompetensi KewirausahaanTerhadap Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM)(Studi Empiris pada UMKM di Kabupaten Rokan Hilir) - Putri, Sri Melisa; Desmiyawati; Hariadi (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
Abstract. This study aims to examine: (1) the effect of competitive advantage on the performance of MSMEs, (2) the effect of entrepreneurial competence on the performance of MSMEs. The population in this study were all MSMEs registered at the Office of Cooperatives and UKM, Rokan Hilir Regency. In this study, the sample used was 100 MSMEs which were calculated using the Slovin formula using the side purposive method. This study uses primary data with a questionnaire. The analytical method used in this research is multiple linear regression analysis. The analytical tool used in this study is Statistical Product and Service Solution (SPSS) version 23.0. The results of this study indicate that: (1) competitive advantages affects the performances of MSMEs with a significant level of 0.019 < 0.05, (2) entrepreneurial competence affects the performance of MSMEs with significant level 0.000 < 0.05. This shows that the variable competitive advantage (X1) and entreprenurial competence (X2) have a significant and positive effect on the performance of MSMEs (Y). Keywords: Competitive Advantage, Entrepreneurship Competence, Performance of Micro, Small and Medium Enterprises (MSMEs)